Social Networking Sites: The relationship element in the communication mix - Langaro, D.; Salgueiro, M.F.; Rita, P. (Proceedings of the 44th European Marketing Academy Conference (EMAC), 2015)
Social Networking Sites (SNS) offer a new way for brands to interact with their markets and establish one-to-one relationships in mass consumption contexts. Focusing on brands from consumer packaged goods (CPG), the current study builds on the argument that SNS are important relationship channels for CPG brands, as they provide positive relational consequences. The theoretical model proposed evaluates the impact of users´ participation at SNS on brand trust and affective commitment. An online quantitative survey was implemented with 575 users of CPG´ brand like pages at Facebook. Structural equation modeling was used to test the research hypotheses. The findings help to validate SNS as a relationship marketing channel able to generate stronger consumer-brand relationships, with special impact on brand trust. Managerial and theoretical implications are discussed.